Chemical and electronic structure of the heavily intermixed (Cd, Zn)S:Ga/CuSbS2 interface. (17th July 2022) - Hartmann, C.; Brandt, R. E.; Baranowski, L. L.; Köhler, L.; Handick, E.; Félix, R.; Wilks, R. G.; Zakutayev, A.; Buonassisi, T.; Bär, M.
Abstract : Hard X-ray photoelectron spectroscopy reveals the (Cd, Zn)S:Ga/CuSbS2 thin-film solar cell interface to be heavily intermixed resulting in a 'cliff'-like conduction band offset. Abstract : The interface formation and chemical and electronic structure of the (Cd, Zn)S:Ga/CuSbS2 thin-film solar cell heterojunction were studied using hard X-ray photoelectron spectroscopy (HAXPES) of the bare absorber and a buffer/absorber sample set for which the buffer thickness was varied between 1 and 50 nm. We find a heavily intermixed interface, involving Cu, Zn, and Cd as well as significant Ga and Cu profiles in the buffer. The valence band (VB) offset at the buffer/absorber interface was derived as (−1.3 ± 0.1) eV, which must be considered an upper bound as the Cu diffused into the buffer might form a Cu-derived VB maximum located closer to the Fermi level. The estimated conduction band minimum was 'cliff'-like; a situation made more severe considering the Cu-deficiency found for the CuSbS2 surface. The complex interface structure's effect on the performance of (Cd, Zn)S:Ga/CuSbS2 -based solar cells and its limitation is discussed together with possible mitigation strategies.